Identity and Gender Perspective of Gatotkaca through Transmedia Narrative in Character Design for Game - Ardiyan Ardiyan (Bina Nusantara University, 2017)
Indonesian games are still need improvement, this matter is indicated by the quantity and the quality of the product. One of the quality game aspect is character design which has big influence in visual assets development. The contemporary spirit to develop creativity in cultural aspect through many media has opened many possibilities to breakfree from the traditional form in Indonesia, especially wayang, that commonly considered as sacred which has made the audiences lost their interest. This research was made to study the game character design of Ghatotkacha in Boma Naraka Sura PC Game by Anantarupa Studio which is using cultural story of wayang. This game had significant support in crowdfunding. In descriptive interpretive analysis from cultural identity and gender stereotyping perpective through transmedia narrative, Gatotkaca character design has evolved from narrative into visual form that is being marked by eminent artworks.Â